Fellow Efficiency During Anterior Cruciate Ligament Reconstruction Improves Over Time, Yet Is Less Than Experienced Physician Assistant But With No Significant Difference in Patient-Reported Outcomes - Sean M. Hazzard, P.A., M.B.A; Donna M. Scarborough, Ph.D; Eric M. Berkson, M.D; Peter D. Asnis, M.D (Elsevier, 2023)
Purpose: To evaluate the intraoperative efficiency and patient outcomes of anterior cruciate ligament reconstruction (ACLR) assisted by a sports medicine fellow over the course of the academic year compared with an experienced physician assistant (PA). Methods: A single-surgeon cohort of primary ACLRs with either bone-tendon-bone autograft or bone-tendon-bone allograft (without any other significant time-consuming procedures such as meniscectomy/repair) were evaluated using a patient registry system over 2 years assisted by an experienced PA compared with an orthopaedic surgery sports medicine fellow. There were 264 primary ACLRs included in this study. Outcomes included evaluation of surgical time, tourniquet time, and patient-reported outcome measures. Results: The surgical efficiency of the fellow (as measured by surgical time and tourniquet time) improved over each academic quarter. Patient-reported outcomes between the 2 first-assist groups showed no significant difference over 2 years with both ACL graft groups combined. ACLRs assisted by the PA showed shorter tourniquet times by 22.1% and shorter total surgical times by 11.9% compared with the sports medicine fellows when both grafts were combined (P < .001). The surgical and tourniquet times (minutes) for the fellow (standard deviation of surgical time 19.5-25.0 and tourniquet time 19.5-25.0) did not average out to be more efficient in any of the 4 quarters of the year compared with the PA-assisted group (standard deviation of surgical time 14.4-14.8 and tourniquet time 14.8-22.4). Autografts showed more efficient tourniquet (18.7%) and skin-to-skin surgical times (11.1%) in the PA group compared with the fellow group (P < .001). Allografts showed more efficient tourniquet (37.7%) and skin-to-skin surgical times (12.8%) in the PA group compared with the fellow group (P < .001). Conclusions: The surgical efficiency of the fellow during primary ACLRs improves over the academic year. Patient-reported outcomes are similar in cases assisted by the fellow compared with an experienced physician assistant. Cases assisted by the PA were performed more efficiently compared with the sports medicine fellow. Clinical Relevance: The intraoperative efficiency of a sports medicine fellow objectively improves over the academic year for primary ACLRs but may not be as efficient as an experienced advanced practice provider; however, there appears to be no significant differences in patient-reported outcome measures between the 2 groups. This helps quantify the time commitment for attendings and academic medical institutions as the "cost of education" of trainees such as fellows.